Subalgebras of BCK/BCI-Algebras Based on Cubic Soft Sets - G. Muhiuddin; Feng Feng; Young Bae Jun (The Scientific World Journal)
Operations of cubic soft sets including “AND” operation and “OR” operation based on P-orders and R-orders are introduced and some related properties are investigated. An example is presented to show that the R-union of two internal cubic soft sets might not be internal. A sufficient condition is provided, which ensure that the R-union of two internal cubic soft sets is also internal. Moreover, some properties of cubic soft subalgebras of BCK/BCI-algebras based on a given parameter are discussed.